Assess the effectiveness of cryotherapy on arterio Venous fistula puncture site pain among Patients on haemodialysis - S.BENIN SUNDAR,; DR. P.MANGALA GOWRI,; DR. S.ARUNA, (International Journal of Pharma and Bio Sciences, 2017)
This study was intended to evaluate the effectiveness of cryotherapy on Arterio Venous Fistula puncture site pain among patients on Haemodialysis. A Quasi-experimental design (pre-post test) was used. 60 samples were selected by convenient sampling technique, 30 were divided each in the experimental and control group. Demographic variable was collected by using structured questionaire then the pre test level of pain during AV fistula puncture site was assessed by numerical pain rating scale to both groups.The second day the experimental group patients was given cold application and the control group patients was continue the routine treatment.post test level of pain was assessed for both experimental and control group. Findings: In pre test, In experimental group, 14(46.67%) had moderate, 10(33.33%) had severe and 6(20%) had mild level of pain. In control group 15(50%) had moderate, 10(33.33%) had severe and 5(16.67%) had mild level of pain. In post test, In experimental group 14(46.67%) had mild, 13(43.33%) had moderate and only 3(10%) had severe level of pain. In control group, 16(53.33%) had moderate, 9(30%) had severe and 5(16.67%) had mild level of pain. It was statistically significant at P < 0.001. Total number of dialysis session attended had shown statistically significant association with post test level of pain in the experimental group at p<0.05 level.Conclusion: This study indicates that cryotherapy is a simple non-pharmacological and cost effective method. It is effective in reducing pain among Haemodialysis patients with AV Fistula puncture site pain.